2013
DOI: 10.15261/serdj.20.65
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Paclitaxel Production by Addition of Water-Soluble 5-Aminolevulinic Acid and <i>In Situ </i>Extraction with Lauryl Alcohol in A Suspension Callus Culture

Abstract: A fatty alcohol, lauryl alcohol (LA), has been found to be an effective organic solvent for in situ extraction and production of paclitaxel in a suspension plant cell culture.The culture procedure and/or conditions for enhancing paclitaxel productivity by avoiding feed-back inhibition have been studied. 5-aminolevulinic acid (ALA), which promotes plant growth, was used for this purpose in the LA-medium two phase culture systems and its effect on the paclitaxel productivity in the culture was examined. Similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…In addition, sequential refreshment of LA including MJ [14] must be suitable for this purpose in the present culture systems. We also reported that water-soluble 5-aminolevulinic acid (ALA), which promoted the growth and yield of the plant [23][24][25], had positive effects on the callus growth and biosynthesis of paclitaxel [26]. The culture conditions in the LA-medium two phase culture systems including ALA and MJ for efficient callus growth and higher taxane production are under investigation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, sequential refreshment of LA including MJ [14] must be suitable for this purpose in the present culture systems. We also reported that water-soluble 5-aminolevulinic acid (ALA), which promoted the growth and yield of the plant [23][24][25], had positive effects on the callus growth and biosynthesis of paclitaxel [26]. The culture conditions in the LA-medium two phase culture systems including ALA and MJ for efficient callus growth and higher taxane production are under investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to isolate and purify these valuable molecules from plants is key to elucidating their potential applications. For example, the anti-cancer drug, paclitaxel, which was initially extracted from bark from the Pacific yew tree, continues to have efforts developed to improve its extraction efficiency from plant cell cultures (Theodoridis et al, 1998; Kawamura et al, 1999; Oh et al, 2012; Taura et al, 2013; Kim and Kim, 2015). This reiterates the points made in the introduction, that the more complex the target terpene becomes, the more complex the extraction procedure can be to optimize recovery, fully.…”
Section: Commentarymentioning
confidence: 99%
“…Cells were collected from cultures, washed with water, blotted on filter paper to remove excess liquid, and then weighed to determine the fresh cells weight. The amounts of the taxanes in the medium phase, the IL phase and the cells in all samples were analyzed by using a reversed-phase HPLC system according to the analytical procedures as described previously [4]. Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a problem of feedback-inhibition of the PTX. Two phase culture systems using water-immiscible liquids such as organic solvents and ionic liquids (ILs) have been proposed for the in situ extraction of hydrophobic PTX from the culture medium via their hydrophobic interaction to decrease the PTX's inhibition, [3][4]. We reported on the use of more hydrophobic organic solvents such as lauryl alcohol and ILs such as 1-hexyl-3-methylimidazolium hexafluorophosphate (HMIM-PF 6 ) for the in situ extraction of paclitaxel from the aqueous medium [5][6].…”
Section: Introductionmentioning
confidence: 99%